ANALYSIS OF THEME AND RHEME ON UNIVERSITY STUDENTS’ WRITING - wafda raudhatul hilyah; Rama Dwika Herdiawan; Raynesa Noor Emiliasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2022)
The purpose of this study was to investigate the types of themes and describe the most dominant themes used in students' writing. The data used were from 5 students who wrote on the subject of writing introductory paragraphs and the data were analyzed based on Halliday & Matthiessen's MA K Theory (2014). This research was conducted using a discourse analysis. Data collection is done by observation and document study. Data was collected from the writings of the first semester at Majalengka University. The research found various themes: topical, textual, interpersonal, marked and unsigned themes. And the most dominant type of theme is characterized by topical themes and themes. Patterns of theme realization were found in students writing texts namely topical themes, textual-topical themes and interpersonal-topical themes. Meanwhile, only a few topical-textual interpersonal. The students use most of the topic clauses as themes starting with a word or phrase that functions as a subject and addition. All types of themes are used in writing student texts, except interpersonal themes (addition of vocative, addition of modals and limited verbal operators) and some textual themes (addition continues and continues). Therefore, in the Theme-Rheme structure of a text clause by clause, to gain insight into its texture and how the writer clarifies the nature of the fixing that completes it.